Religious education in pre-modern Europe - Tanaseanu-Döbler, Ilinca.; Döbler, Marvin. (Numen Book Series, 2012)
Although religious education is a much-debated topic in present-day History of Religions, its study focuses almost exclusively on contemporary phenomena. Furthermore, this field of study still lacks a comprehensive theoretical framework to structure research. The volume presented here explores religious education from a historical perspective, focusing on source material from pre-modern Europe. Scholars from the History of Religions, Theology, Classical Philology, Medieval Studies and Byzantine Studies contribute their expertise to analyse selected aspects of religious education in Antiquity, Byzantium and the Middle Ages, highlighting the diverse concepts of education, educational contents, actors, media, methods, ideals and intentions at play, and anchoring their case studies in the broader panorama of European history. Based on this material, the editors propose a systematic framework to map the research field.